ANALYSIS OF RELIABILITY OF ELECTRICITY SUPPLY OF LIGHTS OF LIGHT SIGNAL SYSTEMS OF CIVIL AVIATION AIRPORTS - Дев’яткіна, С. С. (Proceedings of National Aviation University (archive), 2021)
The results of the comparative analysis of the reliability of the power supply system of aerodrome lights of modern light signal systems of aerodromes of civil aviation are offered. Various power supply schemes with redundancy of cable lines and without redundancy are considered. An assessment of the technical and economic efficiency of redundancy of cable lines of aerodrome lights from the standpoint of the impact of redundancy on flight safety at the stage of visual piloting in difficult weather conditions.